Exploring the best strategy plan for improving the digital convergence by using a hybrid MADM model - Hsu, Wan-Chi Jackie; Tsai, Ming-Hone; Tzeng, Gwo-Hshiung (Technological and Economic Development of Economy, 2018)
This study proposes a new hybrid MADM model that can explore the best strategy plan according to the environmental attributes that influence digital convergence, with the additional consideration of societal and individual needs for improving the digital convergence toward satisficing users’ needs. The proposed hybrid MADM model employs the DEMATEL method to construct an influential network relationship map (INRM), and find the influential weights of DANP (DEMATEL-based ANP). Next, a modified VIKOR method is employed to assess the weighting of identified attributes to integrate the performance gap for each criterion into dimensions and the overall. Finally, this paper presents Taiwan as an empirical case to demonstrate the effectiveness of the proposed model in practically improving laws and regulations to plan for digital convergence. The contributions of our proposed model can be summarized as follows: (1) The INRM can be used to assist government bodies in understanding the influence and relationships of digital convergence development; (2) The modified VIKOR can be employed to reduce performance-gap towards achieving the aspiration level; (3) The model can help decision-makers to avoid choosing the optimal inferior alternative for reaching a certain aspiration level through continuous improvement.First published online 9 January 2017